2003
DOI: 10.1183/09031936.03.00004608
|View full text |Cite
|
Sign up to set email alerts
|

Muscle wasting and changes in muscle protein metabolism in chronic obstructive pulmonary disease

Abstract: Muscle wasting and changes in muscle protein metabolism in chronic obstructive pulmonary disease. R.T. Jagoe, M.P.K.J. Engelen. #ERS Journals Ltd 2003. ABSTRACT: Loss of skeletal muscle mass is now recognised as an important feature of chronic obstructive pulmonary disease (COPD) which contributes to symptoms and influences prognosis. The changes in skeletal muscle remain poorly understood, largely because only a few studies have been performed to define the adaptations in whole body and muscle protein metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
1
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 134 publications
(178 reference statements)
5
86
1
6
Order By: Relevance
“…Similar observation were reported by several investigators 15,[24][25][26][27][28] . In addition, significant improvement in mean Borg score was observed in PR intervened patients but it was not improved in patients without PR after 60 days.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar observation were reported by several investigators 15,[24][25][26][27][28] . In addition, significant improvement in mean Borg score was observed in PR intervened patients but it was not improved in patients without PR after 60 days.…”
Section: Discussionsupporting
confidence: 80%
“…But literature review suggested that, decreased skeletal muscle mass in the periphery may cause loss of endurance and strength of peripheral muscles to produce decrement in 6MWD in COPD patients 24 . Moreover, restricted working capability for dyspnea may produce disuse atrophy in the peripheral limb muscles which may act as a factor for decrement in peripheral muscle load and muscle wasting in stable COPD patients may cause decrement in overall skeletal muscle mass which may produce exercise intolerance 25 . Again, hyperinflation and overstretching of the alveoli and airway may decrease diffusing membrane surface area for gaseous exchange and diffusing capacity of respiratory membrane in COPD patients may cause decreased oxygenation of blood and ultimately decreased systemic arterial SpO 2 % and increased PCO 2 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Both obesity and cigarette smoking are also important risk factors in many age-related diseases, accelerating the aging process via increasing oxidative stress and inflammation (51). It has been hypothesized (32,52) that weight loss associated with chronic obstructive pulmonary disease commonly observed in long-term smokers is actually due to lean body mass loss. This study, for the first time, examined the combined effects of these two detrimental behaviors, cigarette smoking and consumption of an energy-dense, high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that, long standing alveolar hypoventilation and dyspnea in the COPD patients may cause increased work of breathing, hypoxia induced decreased ATP production and increased energy expenditure followed by skeletal muscle wasting in these groups of patients. [27][28][29][30] On the other hand, expiratory airflow limitation due to decrease elastic fibres in the alveolar walls and airways have also been suggested as an important contributory factor for lung hyperinflation in this group of patients. As a consequence, there may be increase in inspiratory airflow resistance followed by derangement of ventilatory variables.…”
Section: Discussionmentioning
confidence: 99%